Global Health Risk Framework: Governance for Global Health: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak.
Keywords: Health and Medicine

Global Health Impacts of Vector-Borne Diseases: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Pathogens transmitted among humans, animals, or plants by insects and arthropod vectors have been responsible for significant morbidity and mortality throughout recorded history. Such vector-borne diseases – including malaria, dengue, yellow fever, and plague – together accounted for more human disease and death in the 17th through early 20th centuries than all other causes combined. Over the past three decades, previously controlled vector-borne diseases have resurged or reemerged in new geographic locations, and several newly identified pathogens and vectors have triggered disease outbreaks in plants and animals, including humans.
Keywords: Health and Medicine

Enabling Rapid and Sustainable Public Health Research During Disasters: Summary of a Joint Workshop by the Institute of Medicine and the U.S. Department of Health and Human Services - Institute of Medicine (The National Academies Press, 2015)
Over the past decade, preparedness and response capacities of government agencies, hospitals and clinics, public health agencies, and academic researchers in the United States and abroad have been challenged by a succession of public health emergencies, ranging from radiological threats to pandemics to earthquakes. Through After Action Reports, each of these emergencies has yielded important information and lessons learned that can inform future disaster response and recovery efforts. However, important information that needs to be collected during and immediately following these emergencies is often missed because of barriers and obstacles to gathering such data, such as varying institutional review board restrictions in different states, no sustainable funding network for this type of work, uncertainty on who should be involved in research response, and a lack of knowledge around how best to integrate research into response and recovery frameworks. Taking action to enable medical and public health research during disasters was the focus of a workshop held on June 12 and 13, 2014, coordinated and supported jointly by the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events, National Institute of Environmental Health Sciences, the National Library of Medicine, the U.S. Department of Health and Human Services' Office of the Assistant Secretary for Preparedness and Response, and the Centers for Disease Control and Prevention. Invited speakers and participants from federal, state, and local government, academia, and community and worker organizations came together to discuss how to integrate research into existing response structures; identify critical research needs and priorities; identify obstacles and barriers to research; discuss structures and strategies needed for deployment of a research study; share ideas, innovations, and technologies to support research; and explore data collection tools and data-sharing mechanisms for both rapid and longitudinal research. Enabling Rapid and Sustainable Public Health Research During Disasters summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Global Health Risk Framework: Resilient and Sustainable Health Systems to Respond to Global Infectious Disease Outbreaks: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak.
Keywords: Health and Medicine

Engaging the Private-Sector Health Care System in Building Capacity to Respond to Threats to the Public's Health and National Security: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Disasters tend to cross political, jurisdictional, functional, and geographic boundaries. As a result, disasters often require responses from multiple levels of government and multiple organizations in the public and private sectors. This means that public and private organizations that normally operate independently must work together to mount an effective disaster response. To identify and understand approaches to aligning health care system incentives with the American public’s need for a health care system that is prepared to manage acutely ill and injured patients during a disaster, public health emergency, or other mass casualty event, the National Academies of Sciences, Engineering, and Medicine hosted a 2-day public workshop on March 20 and 21, 2018. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Gain-of-Function Research: Summary of the Second Symposium, March 10-11, 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On March 10-11, 2016, the National Academies of Sciences, Engineering, and Medicine held a public symposium on potential U.S. government policies for the oversight of gain-of- function (GOF) research. This was the Academies' second meeting held at the request of the U.S. government to provide a mechanism to engage the life sciences community and the broader public and solicit feedback on optimal approaches to ensure effective federal oversight of GOF research as part of a broader U.S. government deliberative process.
Keywords: Health and Medicine

Crossing the Global Quality Chasm: Improving Health Care Worldwide - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
In 2015, building on the advances of the Millennium Development Goals, the United Nations adopted Sustainable Development Goals that include an explicit commitment to achieve universal health coverage by 2030. However, enormous gaps remain between what is achievable in human health and where global health stands today, and progress has been both incomplete and unevenly distributed. In order to meet this goal, a deliberate and comprehensive effort is needed to improve the quality of health care services globally. Crossing the Global Quality Chasm: Improving Health Care Worldwide focuses on one particular shortfall in health care affecting global populations: defects in the quality of care. This study reviews the available evidence on the quality of care worldwide and makes recommendations to improve health care quality globally while expanding access to preventive and therapeutic services, with a focus in low-resource areas. Crossing the Global Quality Chasm emphasizes the organization and delivery of safe and effective care at the patient/provider interface. This study explores issues of access to services and commodities, effectiveness, safety, efficiency, and equity. Focusing on front line service delivery that can directly impact health outcomes for individuals and populations, this book will be an essential guide for key stakeholders, governments, donors, health systems, and others involved in health care.
Keywords: Health and Medicine

Global Health and the Future Role of the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
While much progress has been made on achieving the Millenium Development Goals over the last decade, the number and complexity of global health challenges has persisted. Growing forces for globalization have increased the interconnectedness of the world and our interdependency on other countries, economies, and cultures. Monumental growth in international travel and trade have brought improved access to goods and services for many, but also carry ongoing and ever-present threats of zoonotic spillover and infectious disease outbreaks that threaten all.
Keywords: Health and Medicine

Emerging Viral Diseases: The One Health Connection: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In the past half century, deadly disease outbreaks caused by novel viruses of animal origin - Nipah virus in Malaysia, Hendra virus in Australia, Hantavirus in the United States, Ebola virus in Africa, along with HIV (human immunodeficiency virus), several influenza subtypes, and the SARS (sudden acute respiratory syndrome) and MERS (Middle East respiratory syndrome) coronaviruses - have underscored the urgency of understanding factors influencing viral disease emergence and spread. Emerging Viral Diseases is the summary of a public workshop hosted in March 2014 to examine factors driving the appearance, establishment, and spread of emerging, re-emerging and novel viral diseases; the global health and economic impacts of recently emerging and novel viral diseases in humans; and the scientific and policy approaches to improving domestic and international capacity to detect and respond to global outbreaks of infectious disease. This report is a record of the presentations and discussion of the event.
Keywords: Health and Medicine

The Use and Effectiveness of Powered Air Purifying Respirators in Health Care: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Protecting 18 million United States health care workers from infectious agents - known and unknown - involves a range of occupational safety and health measures that include identifying and using appropriate protective equipment. The 2009 H1N1 influenza pandemic and the 2014 Ebola virus outbreak in West Africa have called raised questions about how best to ensure appropriate and effective use of different kinds of personal protective equipment such as respirators, not only to promote occupational safety but also to reduce disease transmission. The Use and Effectiveness of Powered Air Purifying Respirators in Health Care is the summary of a workshop convened by the Institute of Medicine Standing Committee on Personal Protective Equipment for Workplace Safety and Health to explore the current state of practices and research related to powered air purifying respirator (PAPRs) and potential updates to performance requirements. Presentations and discussions highlighted current health care practices using PAPRs and outlined the research to date on the use and effectiveness of PAPRs in health care settings with a focus on the performance requirements. The Use and Effectiveness of Powered Air Purifying Respirators in Health Care focuses on efficacy, current training, maintenance, supplies, and possible enhancements and barriers to use in inpatient, clinic, nursing home, and community (home) settings. This report also explores the strengths and weaknesses of using various approaches to health care PAPR standards.
Keywords: Health and Medicine

Global Health Risk Framework: Pandemic Financing: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak.
Keywords: Health and Medicine

Global Health Risk Framework: Research and Development of Medical Products: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak.
Keywords: Health and Medicine

Potential Research Priorities to Inform Public Health and Medical Practice for Domestic Zika Virus: Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Given the recent rapid spread of Zika virus (ZIKV) throughout the Americas and the presence of its vector mosquito species within parts of the United States, RADM Nicole Lurie, Assistant Secretary for Preparedness and Response, U.S. Department of Health and Human Services, determined an urgent need for additional research to better characterize ZIKV, especially those issues related to the means of transmission and infection during pregnancy. The National Academies of Sciences, Engineering, and Medicine convened a 1-day public workshop on February 16, 2016, to discuss and explore key factors associated with ZIKV.
Keywords: Health and Medicine

Regional Disaster Response Coordination to Support Health Outcomes: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2015)
When disaster strikes, it rarely impacts just one jurisdiction. Many catastrophic disaster plans include support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple stakeholders together from sectors that do not routinely work with each other can augment a response to a disaster, but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response. As many communities within a region will have similar vulnerabilities, a logical step in planning is to establish responsibilities and capacities, and be able to work toward common goals to address all-hazards when the entire region is affected. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a series of three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required in response to a large scale multijurisdictional disaster. The purpose of each regional workshop was to discuss ways to strengthen coordination among multiple jurisdictions in various regions to ensure fair and equitable treatment of communities from all impacted areas. Regional Disaster Response Coordination to Support Health Outcomes summarizes the presentation and discussion of these workshops.
Keywords: Health and Medicine; Conflict and Security Issues

Vector-Borne Diseases: Understanding the Environmental, Human Health, and Ecological Connections: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
Vector-borne infectious diseases, such as malaria, dengue fever, yellow fever, and plague, cause a significant fraction of the global infectious disease burden; indeed, nearly half of the world's population is infected with at least one type of vector-borne pathogen (CIESIN, 2007; WHO, 2004a). Vector-borne plant and animal diseases, including several newly recognized pathogens, reduce agricultural productivity and disrupt ecosystems throughout the world. These diseases profoundly restrict socioeconomic status and development in countries with the highest rates of infection, many of which are located in the tropics and subtropics.
Keywords: Health and Medicine; Conflict and Security Issues

The Influence of Global Environmental Change on Infectious Disease Dynamics: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
The twentieth century witnessed an era of unprecedented, large-scale, anthropogenic changes to the natural environment. Understanding how environmental factors directly and indirectly affect the emergence and spread of infectious disease has assumed global importance for life on this planet. While the causal links between environmental change and disease emergence are complex, progress in understanding these links, as well as how their impacts may vary across space and time, will require transdisciplinary, transnational, collaborative research. This research may draw upon the expertise, tools, and approaches from a variety of disciplines. Such research may inform improvements in global readiness and capacity for surveillance, detection, and response to emerging microbial threats to plant, animal, and human health. The Influence of Global Environmental Change on Infectious Disease Dynamics is the summary of a workshop hosted by the Institute of Medicine Forum on Microbial Threats in September 2013 to explore the scientific and policy implications of the impacts of global environmental change on infectious disease emergence, establishment, and spread. This report examines the observed and potential influence of environmental factors, acting both individually and in synergy, on infectious disease dynamics. The report considers a range of approaches to improve global readiness and capacity for surveillance, detection, and response to emerging microbial threats to plant, animal, and human health in the face of ongoing global environmental change.
Keywords: Health and Medicine; Conflict and Security Issues

What You Need to Know About Infectious Disease - Institute of Medicine (The National Academies Press, 2011)
About a quarter of deaths worldwide--many of them children--are caused by infectious organisms. The World Health Organization reports that new infectious diseases are continuing to emerge and familiar ones are appearing in new locations around the globe. What's behind this trend? How can invisible organisms cause such harm? And to what extent has human behavior amplified the problem? What You Need to Know About Infectious Disease provides an overview of infectious disease, drawing on reports of the Institute of Medicine. Written for a general audience, it describes the biology, history, and future trends of some of the world's most widespread and harmful infections and explains what we need to do--as individuals and as a society--to address this global challenge.
Keywords: Health and Medicine

Supporting Family and Community Investments in Young Children Globally: Summary of a Joint Workshop by the National Academies of Sciences, Engineering, and Medicine and the Ethiopian Academy of Sciences - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
To examine the science, policy, and practice surrounding supporting family and community investments in young children globally and children in acute disruptions, the National Academies of Sciences, Engineering, and Medicine held a workshop in partnership with the Ethiopian Academy of Sciences in Addis Ababa, Ethiopia, from July 27-29, 2015. The workshop examined topics related to supporting family and community investments in young children globally. Examples of types of investments included financial and human capital. Participants also discussed how systems can better support children, families, and communities through acute disruptions such as the Ebola outbreak. Over the course of the 3-day workshop, researchers, policy makers, program practitioners, funders, young influencers, and other experts from 19 countries discussed how best to support family and community investments across areas of health, education, nutrition, social protection, and other service domains. This report summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences; Health and Medicine

Infectious Disease Movement in a Borderless World: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Modern transportation allows people, animals, and plants--and the pathogens they carry--to travel more easily than ever before. The ease and speed of travel, tourism, and international trade connect once-remote areas with one another, eliminating many of the geographic and cultural barriers that once limited the spread of disease. Because of our global interconnectedness through transportation, tourism and trade, infectious diseases emerge more frequently; spread greater distances; pass more easily between humans and animals; and evolve into new and more virulent strains. The IOM's Forum on Microbial Threats hosted the workshop "Globalization, Movement of Pathogens (and Their Hosts) and the Revised International Health Regulations" December 16-17, 2008 in order to explore issues related to infectious disease spread in a "borderless" world. Participants discussed the global emergence, establishment, and surveillance of infectious diseases; the complex relationship between travel, trade, tourism, and the spread of infectious diseases; national and international policies for mitigating disease movement locally and globally; and obstacles and opportunities for detecting and containing these potentially wide-reaching and devastating diseases. This document summarizes the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Integrating Clinical Research into Epidemic Response: The Ebola Experience - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The 2014–2015 Ebola epidemic in western Africa was the longest and most deadly Ebola epidemic in history, resulting in 28,616 cases and 11,310 deaths in Guinea, Liberia, and Sierra Leone. The Ebola virus has been known since 1976, when two separate outbreaks were identified in the Democratic Republic of Congo (then Zaire) and South Sudan (then Sudan). However, because all Ebola outbreaks prior to that in West Africa in 2014–2015 were relatively isolated and of short duration, little was known about how to best manage patients to improve survival, and there were no approved therapeutics or vaccines. When the World Heath Organization declared the 2014-2015 epidemic a public health emergency of international concern in August 2014, several teams began conducting formal clinical trials in the Ebola affected countries during the outbreak.
Keywords: Health and Medicine